MiRNA engineering of CHO cells facilitates production of difficult‐to‐express proteins and increases success in cell line development. Issue 7 (18th April 2017) - Fischer, Simon; Marquart, Kim F.; Pieper, Lisa A.; Fieder, Juergen; Gamer, Martin; Gorr, Ingo; Schulz, Patrick; Bradl, Harald
ABSTRACT: In recent years, coherent with growing biologics portfolios also the number of complex and thus difficult‐to‐express (DTE) therapeutic proteins has increased considerably. DTE proteins challenge bioprocess development and can include various therapeutic protein formats such as monoclonal antibodies (mAbs), multi‐specific affinity scaffolds (e.g., bispecific antibodies), cytokines, or fusion proteins. Hence, the availability of robust and versatile Chinese hamster ovary (CHO) host cell factories is fundamental for high‐yielding bioprocesses. MicroRNAs (miRNAs) have emerged as potent cell engineering tools to improve process performance of CHO manufacturing cell lines. However, there has not been any report demonstrating the impact of beneficial miRNAs on industrial cell line development (CLD) yet. To address this question, we established novel CHO host cells constitutively expressing a pro‐productive miRNA: miR‐557. Novel host cells were tested in two independent CLD campaigns using two different mAb candidates including a normal as well as a DTE antibody. Presence of miR‐557 significantly enhanced each process step during CLD in a product independent manner. Stable expression of miR‐557 increased the probability to identify high‐producing cell clones. Furthermore, production cell lines derived from miR‐557 expressing host cells exhibited significantly increased final product yields in fed‐batch cultivation processes without compromising product quality. Strikingly, cells co‐expressing miR‐557 and a DTE antibody achieved a twofold increase in product titer compared to clones co‐expressing a negative control miRNA. Thus, host cell engineering using miRNAs represents a promising tool to overcome limitations in industrial CLD especially with regard to DTE proteins. Biotechnol. Bioeng. 2017;114: 1495–1510. © 2017 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc. Abstract : We established a novel miRNA engineered CHO host cell line constitutively expressing a pro‐productive miRNA (miR‐557) to enhance recombinant protein production. Novel miRNA engineered host cells were tested against negative control host cells. Two different monoclonal antibody candidates (easy‐ and difficult‐to‐express mAbs) were stably transfected followed by an entire cell line development process. We demonstrate that stable expression of miR‐557 enhanced recombinant antibody production in CHO cells without negatively affecting product quality.